Space and Growth - Maria Abreu; Henri L.F. de Groot; Raymond J.G.M. Florax (Tinbergen Institute, 2004)
This paper reviews the empirical literature on growth and convergence that has addressed the importance of spatial factors. An important distinction in this literature is the one between absolute and relative location. The literature on absolute location predominantly uses non-spatial econometric techniques, and is strongly linked to the economic growth literature. In contrast, studies on relative location tend to be weakly linked to theory, but apply relatively sophisticated econometric techniques to account for spatial effects. Most studies of the latter type are regional in nature, although there is a growing interest in extending the analysis to a cross-country setting. Both regional and cross-country studies typically make use of so-called spatial process models. Rather than modelling the impediments of space and distance directly, spatial process models start from exogenously provided information about the spatial structure. Our review shows that th! e usage of simple spatial autoregressive lag and error models abounds in the spatial econometrics literature. We assess the appropriateness of such models, and identify areas of potential concern. The rather weak linkage between theory and operational models, the dominance of 'global' over 'local' spatial association patterns, and the implicit restrictions on spatial interaction induced by many of the habitual specifications of the spatial weights matrix concurrently constitute areas where improvements can be made.
Keywords: O11; O13; O57; R11; R12; 330; economic growth; geography; natural resources; spillovers; spatial econometrics; Wachstumstheorie; Raumwirtschaftstheorie; Ökonometrie